2001
DOI: 10.1038/labinvest.3780268
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Undifferentiated-Type Gastric Carcinoma

Abstract: As the great majority of gastric cancers develop histologically differentiated, and a significant proportion of differentiated-type carcinomas progress to become undifferentiated, both histological types are likely to share several common genetic abnormalities, such as p53 mutations at advanced stages. However, a subset of gastric cancers develop as undifferentiated carcinomas, including signet-ring cell carcinoma and poorly differentiated adenocarcinoma, and the molecular pathogenesis of this tumor type remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 30 publications
2
38
1
Order By: Relevance
“…A few studies have reported TP53 mutations as a late event in the development of poorly cohesive gastric cancer, which was our rationale for using cases of 'gastric cancer with aberrant E-cadherin expression' before 'gastric cancer with aberrant p53 expression' to assign a group for clinical applicability. 47,48 The frequency of this subset best correlates with the gastric cancer-stable group (genomically stable) reported in the Cancer Genome Atlas, 6 and the microsatellite stable/epithelial-mesenchymal transition subtype of the Asian Cancer Research Group. 7 This group constituted 21% of the entire cohort similar to the 20% and 15.3% reported in these studies.…”
Section: Discussionmentioning
confidence: 93%
“…A few studies have reported TP53 mutations as a late event in the development of poorly cohesive gastric cancer, which was our rationale for using cases of 'gastric cancer with aberrant E-cadherin expression' before 'gastric cancer with aberrant p53 expression' to assign a group for clinical applicability. 47,48 The frequency of this subset best correlates with the gastric cancer-stable group (genomically stable) reported in the Cancer Genome Atlas, 6 and the microsatellite stable/epithelial-mesenchymal transition subtype of the Asian Cancer Research Group. 7 This group constituted 21% of the entire cohort similar to the 20% and 15.3% reported in these studies.…”
Section: Discussionmentioning
confidence: 93%
“…In previous reports, the frequency of p53 mutation in the early phase was 37-41 % in welldifferentiated adenocarcinomas, and only 0-4 % in poorly differentiated adenocarcinomas [26][27][28][29]. These reports indicate that p53 mutation is an early event in tumorigenesis for well-differentiated adenocarcinoma, while the mutation is rare in poorly differentiated adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…(Tamura, 2002). Ecadherin is inactivated through any combinations of gene mutation, loss of heterozygosity (LOH), and promoter hypermethylation in gastric cancer, especially that of undifferentiated histological type (Tamura et al, 2001). Recent evidences of frequent silencing of hMLH1, p16, RUNX3, and other tumour suppressor and tumour-related genes by promoter hypermethylation suggests that epigenetic alterations play the most important role in gastric carcinogenesis (Tamura, 2004).…”
mentioning
confidence: 99%